A Marxist Analysis of Kafkaesque Society in Metamorphosis. - Rehan Aslam Sahi (Social Science Review Archives, 2025)
The metamorphosis is a novella which is written by Franz Kafka under the impression of absurdism. But as modern writer’s work, we can observe the taste of other literary theories as well in this novella. The aim of this paper is to point out those key elements that demonstrates our society having economy as its major key pillar. The worth of the person is only being described by the amount of vitality he shows toward family, peers and other social institutions; and this vitality is measured in terms of providence. The extent of capital decides one’s status and role in society that whether he is going to control the other class (the proletariat) or get controlled by other class (the bourgeoisie). This distinction is also somehow illustrated in the novella. This paper is written after in-depth analysis of the novel by keeping the lens of Marxism. The sample is simply the text of the novel, no external source is used for highlighting the elements of the literary theory.